Economics vs. Management: An Analysis of Stance Nouns in the Noun That Pattern - Hong, Ling (Advances in Social Sciences Research Journal, 2023)
English for academic purposes (EAP) has been a hot topic in applied linguistics research in the past three decades. In recent years, many researchers have begun to pay close attention to the study of disciplinary English. The present study attempts to explore the similarities and differences between economics and management, by utilizing English research articles in the two disciplines as corpus data, and by analyzing the employment of stance nouns in the pattern of “noun + that”. The analysis results show that economics and management have a lot in common in research objects, research subjects and ways of knowledge construction, and the two disciplines show certain similarities in the distribution of Noun that pattern. However, the more frequent use of the stance nouns in the semantic group of possibility, evidence and opinion in economics research articles indicates that economics relies more on objective experimental evidence, discovery, and scientific statistical methods to construct knowledge than management does. The results of this study can provide insightful implications for the teaching of economic/management English.